Akodon polopi Jayat et al., 2010 is a senior subjective synomym of Akodon viridescens Braun et al., 2010 - D’elía, Guillermo; Jayat, J. Pablo; Ortiz, Pablo E.; Salazar-Bravo, Jorge; Pardiñas, Ulyses F. J. (Zootaxa, 2011)
Two new taxa of species level were recently named for grass mice of the genus Akodon (Cricetidae, Sigmodontinae) from central Argentina: Akodon polopi Jayat, Ortiz, Salazar-Bravo, Pardiñas et D’Elía, 2010 and Akodon viridescens Braun, Mares, Coyner et Van Den Bussche, 2010. Several lines of evidence show that both taxa refer to the same biological species.